Manzanilla Stretch, on the east coast - Dixon, Steve (Ace Printery, Trinidad, 2009)
A photograph of the Manzanilla stretch off the east coast of Trinidad. The road is deserted and lined on either side with mature coconut palms whose trunks criss-cross one another. On the horizon, at right of the photograph, one can just imagine seeing the crests of waves as they break on the sea shore. The word Manzanilla is derived from the Spanish, Punta Manzanillo, or "a little block of land". The expanse of coconut palms along the Manzanilla beach was called "The Cocal" or "Cocos Bay". Manzanilla is the home of Trinidad's fledgling coconut industry.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Manzanilla; Trees--Trinidad and Tobago; Beaches--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Roads--Trinidad and Tobago